2021
DOI: 10.5937/vojtehg69-29629
|View full text |Cite
|
Sign up to set email alerts
|

Model for selecting a route for the transport of hazardous materials using a fuzzy logic system

Abstract: Introduction/purpose: The paper presents a model for the selection of a route for the transport of hazardous materials using fuzzy logic systems, as a type of artificial intelligence systems. The system presented in the paper is a system for assistance in the decisionmaking process of the traffic service authorities when choosing one of several possible routes on a particular path when transporting hazardous materials. Methods: The route evaluation is performed on the basis of five criteria. Each input variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
0
22
0
3
Order By: Relevance
“…The problem of selecting and evaluating a sustainable supplier is addressed in many works. Analyzing papers [49][50][51] and using review papers [52][53][54] in this example of sustainable supplier selection, it was decided to extract the following set of five basic criteria. These are: c 1 , quality of service; c 2 , pollution control; c 3 , environmental efficiency; c 4, price; and c 5 , corporate social responsibility.…”
Section: Case Studymentioning
confidence: 99%
“…The problem of selecting and evaluating a sustainable supplier is addressed in many works. Analyzing papers [49][50][51] and using review papers [52][53][54] in this example of sustainable supplier selection, it was decided to extract the following set of five basic criteria. These are: c 1 , quality of service; c 2 , pollution control; c 3 , environmental efficiency; c 4, price; and c 5 , corporate social responsibility.…”
Section: Case Studymentioning
confidence: 99%
“…Fuzzy logic techniques are efficient in solving complex, ill-defined problems that are characterized by uncertainty of environment and fuzziness of information [36,37]. Taking into account that disturbances and noises are common sources of uncertainties, it can be concluded that from the aspect of fuzzy implementation this system is highly resistant to noise and disturbance [38,39,40]. The fuzzy membership functions for the input linguistic variables, as well as the output linguistic variable are given in Figure 6.…”
Section: Fuzzy Inference Systemmentioning
confidence: 99%
“…The determination of the subjective weight is based on the opinion of experts or expert groups representing the views of various stakeholders. These are such methods as the direct ranking method (DR) (Goodwin & Wright, 1998;Roberts & Goodwin, 2002;Von Winterfeldt & Edwards, 1986), the point allocation (PA) method (Doyle et al, 1997;Roberts & Goodwin, 2002), the ranking method (Ahn & Park, 2008;Barron, 1992Barron, , 1996Roberts & Goodwin, 2002;Solymosi & Dombi, 1986;Milosevic et al, 2021), methods of programming (Pekelman & Sen, 1974;Shirland et al, 2003;Deng et al, 2004), Delphi method (Hwang & Yoon, 1981), pair-wise comparison (AHP) (Saaty, 1980;Takeda et al, 1987), step-wise weight assessment ratio analysis (SWARA) (Kersuliene et al, 2010), full consistency method (FUCOM) (Pamučar et al, 2018;Pamucar & Ecer, 2020), Level Based Weight Assessment (LBWA) (Žižović & Pamucar, 2019). One of the important problems of subjective methods is an assessment of the consistency of expert opinions.…”
Section: Introductionmentioning
confidence: 99%